36 Month Outcomes of a Generalist Paraprofessional Perinatal Home Visiting Intervention in South Africa - Tomlinson, Mark (Prev Sci, 2016)
Almost all pregnant women (98%) in 24 Cape Town neighborhoods were randomized by neighborhood to: 1) the standard care (SC) condition (n=12 neighborhoods; n=594 pregnant women), or 2) the Philani Intervention Program (PIP) in which home visits by Community Health Workers (CHW) were conducted (n=12 neighborhoods; n=644 pregnant women). At 36 months post-birth (84.6% follow-up) PIP mothers were significantly less depressed at compared to the SC mothers. Children in PIP are significantly less likely to be stunted (24.3% vs 18.1%, p=0.013), to have better vocabularies and are less likely to be hospitalized than children in the SC condition. These data suggest home visits may need to continue for several years post-birth. Sustainable, scalable perinatal intervention models are needed in LMIC.